Drug Hypersensitivity and Anaphylaxis in Cancer and Chronic Inflammatory Diseases: The Role of Desensitizations - Castells, Mariana (Frontiers in Immunology, 2017)
Drug Allergy is a rising problem in the XXI century which affects all populations and races, children and adults, and for which the recognition, diagnosis, management and treatment is still not well standardized. Classical and new chemotherapy drugs, monoclonal antibodies and small molecules to treat cancer and chronic inflammatory diseases are aimed at improving quality of life and life expectancy of patients, but an increasing number of reactions including anaphylaxis precludes their use in targeted populations. Women are more affected by drug allergy and up to 27 % of women with ovarian and breast cancer develop carboplatin allergy after multiple cycles of treatment. Carriers of BRCA genes develop drug allergy after fewer exposures and can present with severe reactions, including anaphylaxis. Atopic patients are at increased risk for chemotherapy and monoclonal antibodies drug allergy and the current patterns of treatment with recurrent and intermittent drug exposures may favor the development of drug allergies. To overcome drug allergy, desensitization has been developed, a novel approach which provides a unique opportunity to protect against anaphylaxis and to improve clinical outcomes. There is evidence that inhibitory mechanisms blocking IgE/antigen mast cell activation are active during desensitization, enhancing safety. Whether desensitization modulates drug allergic and anaphylactic responses facilitating tolerance is currently being investigated. This review provides insight into the current knowledge of drug allergy and anaphylaxis to cancer and chronic inflammatory diseases drugs, the mechanisms of drug desensitization and its applications to personalized medicine.